Diaspora and government welfare spending: Do migrant remittances increase public social protection?. (16th April 2019) - Mina, Wasseem
Abstract: This paper contributes to the debate on the impact of migrant remittances on welfare spending. It empirically examines the influence that remittances have on public social protection (SP) expenditures using macrolevel panel data on a sample of 38 high‐ and middle‐income countries over the period 2005–2014. The paper finds that remittances have a negative influence on public SP expenditures, suggesting that they serve as a private substitute to public SP. The results highlight the importance of remittances to government welfare spending and sustainable development.